A novel, fast and sensitive supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS) method for analysis of arachidonic acid metabolites. Issue 15 (4th July 2018) - Kumari A. Ubhayasekera, S. J.; Acharya, Santosh R.; Bergquist, Jonas
Abstract : A validated method for rapid and reliable measurement of five arachidonic acid metabolites in biofluids using supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS). Abstract : The development of a rapid, sensitive and reliable method for the quantification of bioactive arachidonic acid metabolites (AA-metabolites) in biological samples is quite challenging due to the minute concentration, short half-life and their structural complexity arising from different isomers. In this study, a simple, fast and environmentally friendly supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS) method was developed and validated for simultaneous measurement of five (PGD2, PGE2, PGF2α, 6KetoPGF1α and LTB4 ) AA-metabolites in biological samples. These analytes were extracted by protein precipitation followed by separation and quantification. The analysis was completed within 3 minutes. The matrix matched linear calibration ranged from 0.5–100 ng mL −1 ( r 2 ≥ 0.995), whilst, the limit of quantification of PGD2, PGE2, PGF2α, and LTB4 was 0.5 ng mL −1 and was 2.5 ng mL −1 for 6KetoPGF1α . The interday and intraday precisions of the method were less than 15% while the accuracy of most of the analytes varied between 83 and 109%. Finally, as a proof of concept, the method was successfully applied for the determination of eicosanoids in human samples, which expands the possibility to explore physiological states, disease phenotypes, and novel biomarkers.